Faktor Penentu Tingkat Pengangguran Terbuka Saat Pandemi COVID-19 di Provinsi Jawa Timur Tahun 2021 - Althaf Azhar Rafhi Syahputra; Nurfahmiyati (Bandung Conference Series: Economics Studies, 2022)
Abstract. Deputy for Business and Industry Coordination, Coordinating Ministry of Economy said the workforce affected by COVID-19 is around 3.05 million people (as of June 2, 2020) and estimates that additional unemployment can reach 5.23 million percent. This is in accordance with the survey statement of the Central Statistics Agency the groups most affected by COVID-19 are low-income residents and workers in the informal sector. In the city affected is the business of trade. According to the Official Statistics News in August 2021, the TPT of the young age group population (15-24 years) is the highest TPT reaching 19.55 percent. Meanwhile, the TPT of the old age group (60 years and above) is the lowest, which is 2.73 percent. The same pattern occurred in August 2020 and February 2021. The purpose of this study is to find out what factors can determine the high open unemployment rate in East Java Province. The sample from this study is Regency / City in East Java Province in 2021. The sampling technique used is non probability sampling. The method used is an exploratory quantitative method by performing regression analysis. The results of this study showed that variables in the number of poor people and life expectancy had an insignificant effect on the open unemployment rate, while the old school expectation variable had a significant effect on the open unemployment rate in East Java Province. Abstrak. Deputi Bidang Koordinasi Perniagaan dan Industri, Kementerian Koordinator Perekonomian menyatakan tenaga kerja terdampak COVID-19 sekitar 3,05 juta orang (per 2 Juni 2020) dan memperkirakan tambahan pengangguran bisa mencapai 5,23 juta persen. Hal ini sesuai dengan pernyataan survei Badan Pusat Statistik kelompok yang paling terdampak dari COVID-19 adalah penduduk berpendapatan rendah dan pekerja di sektor informal. Adapun di perkotaan yang terdampak adalah bisnis perdagangan. Menurut Berita Resmi Statistik pada Agustus 2021, TPT penduduk kelompok umur muda (15—24 tahun) merupakan TPT tertinggi mencapai 19,55 persen. Sementara itu, TPT penduduk kelompok umur tua (60 tahun ke atas) merupakan yang paling rendah, yaitu sebesar 2,73 persen. Pola yang sama terjadi pada Agustus 2020 maupun Februari 2021. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor apa saja yang dapat menentukan tingginya tingkat pengangguran terbuka di Provinsi Jawa Timur. Sampel dari penelitian ini adalah Kabupaten/Kota di Provinsi Jawa Timur pada tahun 2021. Teknik sampling yang digunakan adalah non probability sampling. Metode yang digunakan adalah metode kuantitatif eksploratif dengan melakukan analisis regresi. Hasil dari penelitian ini menunjukkan bahwa variabel Jumlah penduduk miskin dan angka harapan hidup berpengaruh tidak signifikan terhadap tingkat pengangguran terbuka, sedangkan variabel harapan lama sekolah berpengaruh signifikan terhadap tingkat pengangguran terbuka di Provinsi Jawa Timur.